Implementation of birth plans integrated into childbirth preparation classes for vaginal birth: a qualitative study of women, their husbands and clinicians' perspectives in Iran - Zaynab Mohaghegh; Mojgan Javadnoori; Mahin Najafian; Simin Montazeri; Parvin Abedi; Ehsan Kazemnejad Leyli; Shahla Bakhtiari (BMC, 2022)
Abstract Background Understanding women's experience of birth planning is necessary for introducing and implementing this process in the Iranian maternity services. This study aims to explore perceptions of birth plan implementation in Iran from the perspective of women, their husbands, and clinicians. Methods This qualitative study was conducted in Iran. Qualitative data were collected from November 2020 to March 2021 by conducting semi-structured in-depth interviews with ten mothers who prepared a birth plan, and 15 key informants (obstetricians, midwives, and husbands) who were involved in the implementation process of birth plans. Data were analyzed using conventional qualitative content analysis. Results Data reduction process resulted in 380 codes that were categorized in 16 subcategories and five main categories. The main categories were "Guide and pattern of preparing for childbirth pathway", "Maternal empowerment and sense of triumph", "Facilitating and enhancing communication", "Successful transition to parenthood and women's satisfaction", and "Challenges associated with implementation of the birth plan". The overarching theme "Birth plan: The missing link in promotion of vaginal birth in Iran" was constructed from these categories. Conclusion Findings of this study highlight the effectiveness of the implementation of birth plan along with childbirth preparation classes for increasing the likelihood of a successful vaginal birth and promoting empowerment and satisfaction in women during the childbirth process. The findings of this study could pave the way for developing, introducing, and implementing of birth plan in Iran.